2014
DOI: 10.1177/0896920514524606
|View full text |Cite
|
Sign up to set email alerts
|

The Circle of Dispossession: Evicting the Urban Poor in Baltimore

Abstract: Although tenant evictions are routine in impoverished urban communities throughout the USA, scholars of housing and urban poverty have consistently overlooked this social problem. Drawing predominantly upon participant observation on eviction crews in Baltimore, this study examines the social drama of eviction, focusing upon the orchestration and execution of the court-ordered physical removal of tenants and their property. I find that property managers delegate the 'dirty work' of dispossession to a disposses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 62 publications
1
61
0
5
Order By: Relevance
“…In Purser's words: “the specter of forced displacement — and homelessness — looms large” (7). At the community level, having entire neighborhoods trapped in a “circle of dispossession” (Purser ) can limit individuals’ inclination to invest in their communities, organize for common goals, form strong ties, and implement collective efficacy (Sampson ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Purser's words: “the specter of forced displacement — and homelessness — looms large” (7). At the community level, having entire neighborhoods trapped in a “circle of dispossession” (Purser ) can limit individuals’ inclination to invest in their communities, organize for common goals, form strong ties, and implement collective efficacy (Sampson ).…”
Section: Discussionmentioning
confidence: 99%
“…In Baltimore, landlords first notify tenants of late rent through an official court process. Work by the Baltimore Public Justice Center analyzed these filings and found that landlords file for failure to pay rent (the first step in eviction) 150,000 times per year in Baltimore city-a shocking figure given that the city contains only 130,000 rental households (PJC 2015; similar estimates are found in Purser 2014 andHartman andRobinson 2003). This means that landlords are serially filing on the same tenants multiple times in the same year.…”
Section: The Eviction Context In the Three Citiesmentioning
confidence: 99%
See 3 more Smart Citations